Aeneas at the Europa Hotel: Canon and Nostalgia in Ilja Leonard Pfeijffer’s Novel Grand Hotel Europa - Krupp, József (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Ilja Leonard Pfeijffer’s novel Grand Hotel Europa (2018), through its explicit and structural references to the Aeneid, not only affirms the canonical status of Virgil’s poem but also raises fundamental questions about the significance of cultural traditions in general. The novel emphasises Aeneas’ status as profugus, connecting him to Europe’s refugee crisis during the 2010s. This essay examines the intertextual character of the novel and the concept of ‘nostalgia’, which proves to be central to its vision of European culture.